(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Writing skill is an important aspect of academic performance as well as subsequent work-related one. In fact, most of the first-year majored students at Tay Do University (TDU) still got many difficulties in writing. This study was conducted to identify common writing problems and find out some ways to improve writing skill. The participants consisted of 74 freshmen at TDU. The main data were obtained from the questionnaire and 15 paragraphs written in English by group of two or three students. The results from the data analysis showed that the common problems that the students committed in their English writing were the way of idea expression, limited vocabulary and grammatical errors. This result also mentioned some ways to improve writing skill as writing an outline, reading books relating to the topic and practicing writing. Thus, the study could contribute to learning and teaching English writing at TDU. Moreover, the result could provide students with valuable information so that they could minimize problems in writing.